In Vivo Effects of Bradykinin B2 Receptor Agonists with Varying Susceptibility to Peptidases - Jean, Mélissa; Gera, Lajos; Charest-Morin, Xavier; Marceau, François; Bachelard, Hélène (Frontiers in Pharmacology, 2016)
We reported evidence of bradykinin (BK) regeneration from C-terminal extended BK sequences that behave as peptidase-activated B2 receptor (B2R) agonists. Further to these in vitro studies, we carried out in vivo experiments to verify hemodynamic effects of BK analogs exhibiting variable susceptibility towards vascular and blood plasma peptidases. Rats were anesthetized and instrumented to record blood pressure and heart rate responses to bolus intravenous (i.v.) injection of increasing doses of BK, B-9972 (D-Arg-[Hyp3,Igl5,Oic7,Igl8]-BK), BK-Arg, BK-His-Leu or BK-Ala-Pro, in the absence or presence of specific inhibitors. In some experiments, pulsed Doppler flow probes measured hindquarter Doppler shift in response to i.v. injections of kinins. BK caused rapid, transient and dose-related hypotensive effects. These effects were potentiated ~15 fold by the angiotensin converting enzyme (ACE) inhibitor, enalaprilat, but extensively inhibited by icatibant (a B2R antagonist) and not influenced by the Arg-carboxypeptidase (CP) inhibitor (Plummer's inhibitor). The hypotensive responses elicited by the peptidase-resistant B2R agonist, B-9972, were not affected by enalaprilat, but were inhibited by icatibant. The hypotensive responses to BK-Arg were abolished by pre-treatment with either the Arg-CP inhibitor or icatibant, pharmacologically evidencing BK regeneration. The hypotensive effects of BK-His-Leu and BK-Ala-Pro, previously reported as ACE-activated substrates, were abolished by icatibant, but not by enalaprilat. In vivo regeneration of BK from these two C-terminally extended analogs with no affinity for the B2R must follow alternative cleavage rules involving unidentified carboxypeptidase(s) when ACE is blocked. The transient hypotensive responses to BK and three tested analogs coincided with concomitant vasodilation (increased Doppler shift signal). Together, these results provide in vivo evidence that interesting hypotensive and vasodilator effects can be extracted from prodrug peptides that behave as peptidase-activated B2R agonists.